Obywatele! W dniu 23. lutego 1946 bohaterska Armia Czerwona [...]. (Gdynia : [s.n.], 1946)
Afisz na część Armii Czerwonej i Stalina.
Keywords: Stalin, Iosif Vissarionovič -- (1878-1953).; Związek Radziecki. -- Raboče-Krestʹânskaâ Krasnaâ Armiâ -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- źródła